ANALISIS ASUHAN KEPERAWATAN KOMBINASI RENDAM SERAI DAN FOOT MASSAGE THERAPY UNTUK MENURUNKAN TEKANAN DARAH PADA LANSIA RT005 RW01 KELURAHAN ULUJAMI JAKARTA SELATAN - Annisa Nabilla, (2023)
Elderly or elderly is someone who has reached the age of 60 years and over. Elderly will cause a person to experience physical, psychological and social changes as a result of the aging process. These changes can include decreased physical functions such as muscle strength, vision and hearing as well as decreased memory function and speed of thinking. One of the changes experienced by the elderly is an increase in vascular resistance so that the elderly tend to be prone to hypertension. Hypertension requires pharmacological and non-pharmacological treatment. One of the non-pharmacological treatments that can be done is to modify lifestyle by soaking lemongrass and foot massage therapy. The purpose of this study was to provide nursing care for the elderly with hypertension through a combination intervention of soaking lemongrass and foot massage therapy at RT005 RW01, Ulujami Village, South Jakarta. This research method is a case study through family nursing care. The intervention was carried out 7 times routinely for 20 minutes. Based on the final evaluation, there was a decrease in blood pressure in clients managed with an average systolic of 148.29 mmHg to 135.29 mmHg and an average diastolic of 101.86 mmHg to 89.29 mmHg. On resume clients decreased average systolic blood pressure from 145 mmHg to 100 mmHg and average diastolic from 132.86 mmHg to 87.14 mmHg. The conclusion of this study is that a combination of soaking lemongrass and foot massage therapy can reduce blood pressure in elderly people with hypertension.